Re/learning Student Teaching Supervision: A Co/autoethnographic Self-Study. Issue 2 (3rd May 2016) - Butler, Brandon M.; Diacopoulos, Mark M.
Abstract: This article documents the critical friendship of an experienced teacher educator and a doctoral student through our joint exploration of student teaching supervision. By adopting a co/autoethnographic approach, we learned from biographical and contemporaneous critical incidents that informed short- and long-term practices. In particular, we learned about supervision from our experiences as student teachers, mentors, and university supervisors. We learned about supervision through experiences and insights as they occurred and from the relational dynamics provided by our critical friendship. We dissect critical moments that resulted in a series of key understandings. Autobiography informs practice: in sharing our biographies, we developed an understanding and vision for the type of supervision practice we wished to enact. Reflection and discussion inform practice: by journaling and discussing the supervision process, we reconsidered and acted upon practice. Finally, critical friends provide transformative insights into practice: we learned from each other through interaction and critique of past actions, current practices and future actions. Our collaboration was instrumental in providing a vision that defined our individual pedagogies of supervision. Consistent with other scholarship on the learning of student teacher supervision, this article promotes the provision of a support space for both novice and experienced supervisors to deconstruct and improve practice.